Korapsyonaryo ang tinipong sariling saliksik ng klaseng Filipino 40 - Fabros, Meecie (Quezon City University of the Philippines, 2014)
Filipino dictionary of corrupt and political terms.
Tinipon ng Klaseng Filipino 40 sa pag gabay ni Ginoong Meecie Fabros.
Keywords: Corruption -- Dictionaries -- Filipino; Political corruption -- Philippines -- Dictionaries -- Filipino